College Students' Experience Utilizing a Food Scholarship Program During the COVID-19 Pandemic. (14th June 2022) - Prajapati, Miteshri; Unruh, Deborah; Dave, Jayna; Castro, Alexandra; Wang, Wanyi; Moore, Carolyn
Abstract: Objectives: In 2020, students reported a high prevalence of food insecurity during the recent coronavirus disease (COVID-19) pandemic at a public university. Despite closure of the campus during the pandemic, a Food Scholarship Program (FSP) continued to provide students with food twice a month to help mitigate food insecurity. The purpose of this study was to assess the diet quality among college students participating in the FSP during the pandemic and their experience with the program using mixed methods. Methods: Students were recruited for this cross-sectional study by email and flyers. Students participating in FSP completed: 1) an online survey including the 6-item USDA food security survey and sociodemographic questions; 2) ASA-24 dietary recall; and 3) Zoom interviews to discuss their experience during the pandemic. In-depth interviews were recorded, transcribed, and coded by two people using thematic analysis. Nutrient intake and Healthy Eating Index (HEI)-2015 scores were calculated. Results: The thirteen participants were primarily females (77%), Asian (54%), graduate students (54%), and average age was 26 years. Food insecurity was high (46%). HEI scores (57 ± 16) indicated diets did not align with the 2015 dietary recommendations. Intake of added sugar (66 ± 24 g/d) averaged 17% (11% - 23%) of total caloric intake and exceeded recommendations of <10% per day. Finances impacted student food choices (40%). Interviews revealed that students decreased shopping frequency (40%), bought more food in bulk (40%), prepared more food at home (40%), reduced take-out food/eating in restaurants (80%), decreased the amount of food eaten (30%), and increased more curbside ordering (20%). Students utilized the FSP primarily for financial reasons (90%) and convenience (30%). Overall, students reported a positive experience (70%) with the FSP. Conclusions: The qualitative responses from the interviews support the quantitative results regarding food insecurity and diet quality. Nevertheless, food insecurity remained high, and diet quality remained suboptimal. More work is warranted to improve food security and diet quality among college students, especially during situations such as COVID-19. Funding Sources: Moore-Khourie Grant, USDA Children's Nutrition Research Center.